2004
DOI: 10.1111/j.1471-4159.2004.02532.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging, gender and APOE isotype modulate metabolism of Alzheimer's Aβ peptides and F2‐isoprostanes in the absence of detectable amyloid deposits

Abstract: Aging and apolipoprotein E (APOE) isoform are among the most consistent risks for the development of Alzheimer's disease (AD). Metabolic factors that modulate risk have been elusive, though oxidative reactions and their by-products have been implicated in human AD and in transgenic mice with overt histological amyloidosis. We investigated the relationship between the levels of endogenous murine amyloid b (Ab) peptides and the levels of a marker of oxidation in mice that never develop histological amyloidosis [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…We recently demonstrated that, unlike human ε3, human ε4 is associated with elevated levels of endogenous murine brain Aβ as a function of aging and gender, even in mice that will therefore never develop cerebral amyloidosis. These data support the conclusion that there exists an effect of ε4 on Aβ upstream of fibrillogenesis (41).…”
Section: How Does Apoe ε4 Increase the Risk For Ad?supporting
confidence: 80%
See 1 more Smart Citation
“…We recently demonstrated that, unlike human ε3, human ε4 is associated with elevated levels of endogenous murine brain Aβ as a function of aging and gender, even in mice that will therefore never develop cerebral amyloidosis. These data support the conclusion that there exists an effect of ε4 on Aβ upstream of fibrillogenesis (41).…”
Section: How Does Apoe ε4 Increase the Risk For Ad?supporting
confidence: 80%
“…This is an important point because human (but not murine) Aβ is reported to be a pro-oxidant (49). We were able to dissociate the isoprostane elevation from the formation of histological amyloid by using mice bearing only endogenous murine APP and Aβ (41). Thus, plaque formation is not a prerequisite for elevation of brain isoprostane levels.…”
Section: Are There Other Plausible Hypotheses For the Pathomechanismsmentioning
confidence: 71%
“…In the studies by Li et al [37], no difference in plaque load was observed between males and females of the same transgenic mice (Tg19959 mice). Plaque load in Tg2576 mice does not vary with gender either, although males are more sensitive to alterations in APOE genotype [56]. Other studies suggest sex differences in Tg mice carrying APP with Swedish and the presenilin-1 A246 mutation.…”
Section: Animalsmentioning
confidence: 84%
“…In mice, it has been shown that Ab induction of oxidation in isolated synaptosomes leads to increased reactive oxygen species formation in mice expressing apoE4 relative to apoE3 [49]. Furthermore, Yao et al [50] found increased levels of F 2 -isoprostanes in brains of apoE4 male mice, but found no genotype differences in female mice. More recently a new body of evidence has emerged, from both human observational and cell culture studies, indicating a role of apoE genotype on oxidative status measures, relevant to the progression of CVD.…”
Section: Apoe Genotype and Oxidative Stressmentioning
confidence: 97%